2017
DOI: 10.1126/scitranslmed.aal4651
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and Staphylococcus epidermidis strain diversity underlying pediatric atopic dermatitis

Abstract: The heterogeneous course, severity, and treatment responses among patients with atopic dermatitis (AD; eczema) highlight the complexity of this multifactorial disease. Prior studies have used traditional typing methods on cultivated isolates or sequenced a bacterial marker gene to study the skin microbial communities of AD patients. Shotgun metagenomic sequence analysis provides much greater resolution, elucidating multiple levels of microbial community assembly ranging from kingdom to species and strain-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
442
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 431 publications
(510 citation statements)
references
References 77 publications
32
442
1
8
Order By: Relevance
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…For example, the arginine catabolic mobile element contributes to the ability of USA300, a methicillin-resistant S. aureus strain, to thrive in the acidic environment of human skin and resist host polyamines, helping to explain this strain’s prevalence in skin and soft tissue infections 93,94 . Recent work has also shown that certain strains of S. aureus are not only associated with more severe atopic dermatitis, but are also sufficient to induce skin inflammation in mice independent of host genetic predisposition 22 . This work revealed that the most common method of describing microbiome composition, with genus- or species-level data, fails to resolve important functional differences among strains, which can result from modest gene gain or loss events or even differences in gene expression among strains.…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human pathogens are auxotrophic for amino acids, which confines their network 4 . S. aureus , a human pathogen commonly found on skin 71 , has been directly associated with the inflammatory skin disease atopic dermatitis. Comparison between lesional and non-lesional skin in patients with atopic dermatitis has shown that the number of S. aureus cells can surpass tenfold in patients with lesional skin 72 .…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…These auxotrophic pathogens therefore rely either on their microbial network or on the host to provide these essential nutrients. Excessive overgrowth of specific strains of S. aureus 71 suggests that nutritional resources have to be provided in sufficient quantities to support this overgrowth. The microbial network would thus have to synthesize and share adequate amounts of nutrients, rendering S. aureus dependent on commensal bacteria of the skin microbiota.…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%